UJI SENSITIVITAS INSULIN PADA MENCIT DENGAN PERLAKUAN SARI BUAH MURBEI (Morus alba) - Adhy Nugroho, Christianto (Biospektrum Jurnal Biologi, 2020)
Non-infectious disease is a problem in the world. One of the infectious diseases is hyperglycemia. This study aims to assess the insulin sensitivity of mulberry to mice. The study used 4 groups of mice, namely: group I became a negative control with Na-CMC treatment, group II became a positive control using metformin treatment, group III used mulberry juice at a dose of 2 g / kg BW, and group IV used a dose of mulberry juice. 4 g / kg BW. The results showed that mulberry juice can increase insulin sensitivity in mice.